Prolactin receptor signaling: A novel target for cancer treatment - Exploring anti-PRLR signaling strategies - Standing, David; Dandawate, Prasad; Anant, Shrikant (Frontiers in Endocrinology, 2023)
Prolactin (PRL) is a peptide hormone mainly secreted from the anterior pituitary gland. PRL is reported to play a role in pregnancy, mammary gland development, immune modulation, reproduction, and differentiation of islet cells. PRL binds to its receptor PRLR, which belongs to a superfamily of the class I cytokine receptor that has no intrinsic kinase activity. In canonical signaling, PRL binding to PRLR induces downstream signaling including JAK-STAT, AKT and MAPK pathways. This leads to increased cell proliferation, stemness, migration, apoptosis inhibition, and resistance to chemotherapy. PRL-signaling is upregulated in numerous hormone-dependent cancers including breast, prostate, ovarian, and endometrial cancer. However, more recently, the pathway has been reported to play a tumor-promoting role in other cancer types such as colon, pancreas, and hepatocellular cancers. Hence, the signaling pathway is an attractive target for drug development with blockade of the receptor being a potential therapeutic approach. Different strategies have been developed to target this receptor including modification of PRL peptides (Del1-9-G129R-hPRL, G129R-Prl), growth hormone receptor/prolactin receptor bispecific antibody antagonist, neutralizing antibody LFA102, an antibody-drug conjugate (ABBV-176) of the humanized antibody h16f (PR-1594804) and pyrrolobenzodiazepine dimer, a bispecific antibody targeting both PRLR and CD3, an in vivo half-life extended fusion protein containing PRLR antagonist PrlRA and albumin binding domain. There are have also been attempts to discover and develop small molecular inhibitors targeting PRLR. Recently, using structure-based virtual screening, we identified a few antipsychotic drugs including penfluridol as a molecule that inhibits PRL-signaling to inhibit PDAC tumor progression. In this review, we will summarize the recent advances in the biology of this receptor in cancer and give an account of PRLR antagonist development for the treatment of cancer.